"Our Duty Was Quite Arduous": History and Archaeology of the Civil War on Little Folly Island, South Carolina - Zierden, Martha; Smith, Steven D.; Anthony, Ronald (Scholar Commons, 1995)
The Charleston Museum Leaflet Number 32.